An empirical analysis of the unemployment rate using Okun’s Law and Philips Curve in two ASEAN countries / Kamal Bahrin Shamsuddin and Maznah Wan Omar - Shamsuddin, Kamal Bahrin; Wan Omar, Maznah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Unemployment is a negative phenomenon of human society found in both developed and developing countries. There is a gap between the effectiveness of economic policies aimed at reducing unemployment rates in developing countries and the average rates of economic growth. This issue needs to be addressed in order to understand the negative phenomenon of unemployment curve on the extent of poverty in a household when taken into consideration the influence of Okun’s Law and Philips Curve. Therefore the objective of this research is to examine between two ASEAN countries (Malaysia and Thailand) on the link between changes in unemployment rate (dependent variable) and inflation as well as the output growth, openness of trade and age dependency ratio (independent variables). There are several questions regarding this study; What factors have affected unemployment? Have the data for both nations shown the impact of inflation and other independent variables on the unemployment rate? Nevertheless the unemployment rate movements were also investigated in the frame of Okun’s Law and Philips Curve. In order to achieve the research objectives, a systematic review analysis was employed and a regression analysis. The results of this research have revealed that unemployment is negatively related to inflation, output growth, and openness of trade and age dependency ratio as well as to confirming Okun’s Law and Philips Curve of both countries. This comparison study for both Malaysia and Thailand was using the data for the period of 1982 till 2015. Based on the results of this study, relevant recommendations were provided as well as comparison with other studies.